A network analysis of self‐reported psychoneurological symptoms in patients with head and neck cancer undergoing intensity‐modulated radiotherapy. Issue 20 (15th August 2022) - Lin, Yufen; Bruner, Deborah W.; Paul, Sudeshna; Miller, Andrew H.; Saba, Nabil F.; Higgins, Kristin A.; Shin, Dong M.; Zhang, Wenhui; Miaskowski, Christine; Xiao, Canhua
Abstract : Background: Patients with head and neck cancer experience psychoneurological symptoms (PNS) (i.e., depression, fatigue, sleep disturbance, pain, and cognitive dysfunction) during intensity‐modulated radiotherapy (IMRT) that decrease their functional status, quality of life, and survival rates. The purpose of this study was to examine and visualize the relationships among PNS within networks over time and evaluate for demographic and clinical characteristics associated with symptom networks. Methods: A total of 172 patients (mean age, 59.8 ± 9.9 years; 73.8%, male; 79.4%, White) completed symptom questionnaires four times, namely, before IMRT (T1), 1 month (T2), 3 months (T3), and 12 months (T4) post IMRT. Network analysis was used to examine the symptom‐symptom relationships among PNS. Centrality indices, including strength, closeness, and betweenness, were used to describe the degrees of symptom network interconnections. Network comparison test was used to assess the differences between two symptom networks. Results: Depression was associated with the other four symptoms, and fatigue was associated with the other three symptoms across the four assessments. Based on the centrality indices, depression (rstrength = 1.3–1.4, rcloseness = 0.06–0.08, rbetweeness = 4–10) was the core symptom in all symptom networks, followed by fatigue. Female gender, higher levels of stress, and no alcohol use were associated with stronger symptom networks in network global strength before IMRT. Conclusion: Network analysis provides a novel approach to gain insights into the relationships among self‐reported PNS and identify the core symptoms and associated characteristics. Clinicians may use this information to develop symptom management interventions that target core symptoms and interconnections within a network. Lay summary: This study describes the symptom–symptom relationships for five common symptoms in patients with head and neck cancer receiving radiotherapy. Depression and fatigue appeared to be two core symptoms that were connected with sleep disturbance, pain, and cognitive dysfunction within a network. Several characteristics (i.e., female, higher stress, no alcohol use) were associated with stronger symptom networks. Précis: Depression and fatigue appear to be two core symptoms that are connected with other psychoneurological symptoms. Female gender, higher levels of stress, and no alcohol use are associated with stronger psychoneurological symptom networks.